(untitled) (Applied Biological Research, 2018)
Genetic variation among kidney bean (Phaseolus vulgaris L.) cultivars, procured from the farmers of Kinnaur district of Himachal Pradesh (India), was evaluated using EST-SSR markers. A total of 25 primers were used out of which 19 primers showed amplification. The total n0umber of bands amplified was 26, out of which 24 were polymorphic and 2 were monomorphic. On an average, the number of bands generated primer-1 was 1.37 of which 1.26 was polymorphic and 0.11 were monomorphic. Seven primers produced 14 bands (2 bands primer-1) and only one band each was obtained with remaining primers. The number of unique bands were 2 and the size of amplified product from 70 to 800 bp. Similarity between cultivars estimated as per Jaccard’s coefficients ranged from 0.17-0.90 indicating substantial diversity in bean cultivars. Maximum similarity coefficient (0.90) was between ‘Capsule’ and ‘Kaju’ cultivars while minimum (0.17) between ‘Chitra’ and ‘Luxmi’. Dendrogram grouped cultivars into two major clusters. The PIC value was highest for primer SP5.